International Perspectives on Teaching English in Difficult Circumstances Contexts, Challenges and Possibilities (International Perspectives on English Language Teaching, 2018)
This book offers a holistic practitioner and research-based perspective on English Language Teaching and teacher education in difficult circumstances. In addition to extending the current conceptualization of 'difficult circumstances' in ELT to include the broader policy issues that may affect ELT in low-to-mid income countries, the book focuses on the challenges faced by practitioners and learners in contexts of confinement, conflict and special education. The chapters in this collection examine the challenges and problems that emerge from the complex current ELT environment, and present examples of contextualized inquiry-based strategies and interventions to address these challenges. Underlining the need to extend the boundaries of the discipline of ELT to include teaching-learning in less privileged contexts, this wide-ranging volume will appeal to students, scholars and practitioners of English Language Teaching.